Pengaruh Promosi dan Lokasi terhadap Keputusan Pembelian di Indomaret Pasir Putih Pekanbaru - Ferisca Nurwidyanti; Roma Vita Ria; Jeli Nata Liyas (Jurnal Pemimpin Bisnis Inovatif, 2026)
The purpose of this study is to determine the influence of promotion and location  on consumer purchasing decisions at Indomaret Pasir Putih Pekanbaru. The sample in this study consisted of 96 respondents who are consumers at Indomaret Pasir Putih Pekanbaru. The data analysis method used is multiple linear regression by applying validity test, reliability test, normality test, multicollinearity test, multiple linear regression test, t-test, F-test, and coefficient of determination test (R²) with  the help of SPSS. These tests are conducted to determine the effect of independent  variables on the dependent variable. Based on the results of the study, it shows that partially and simultaneously there is  an influence between the variables of Promotion and Location on Consumer Purchasing Decisions with an effect of 42.9% on consumer purchasing decisions, while  the remaining 57.1% is influenced by other factors outside this study. The regression results show that partially both variables have a significant effect on Consumer  Purchasing Decisions, namely the Promotion variable (X1) where tcount = 4.168 > ttable 1.985 and the significance probability value is 0.000 < 0.05, and the Location variable (X2) where tcount = 4.259 > ttable 1.985 and the significance probability value is 0.000 < 0.05. Simultaneously, the Fcount value is 34.954 with a significance value of 0.000 < 0.05, so it can be concluded that both variables have a significant effect on Consumer Purchasing Decisions. The multiple linear regression equation is as follows:Y = 4.038 + 0.455X1 + 0.395X2 + e.